Performance Measures in Neuroradiology - Seidenwurm, D.; Turski, P.; Barr, J.; Connors, J.; Lev, M.; Mukherji, S.; Russell, E. (American Journal of Neuroradiology, 2007)
SUMMARY: Performance measurement has been added to the Medicare payment scheme as of July 2007. Two performance measures are applicable to neuroradiology, pertaining to brain and vascular imaging in stroke. These measures are early attempts to rigorously define the meaning of effective performance of neuroradiology.